Research Progress on the Correlation Between Epigenetics and Schizophrenia - Chen, Qing; Li, Dan; Jin, Weifeng; Shi, Yun; Li, Zhenhua; Ma, Peijun; Sun, Jiaqi; Chen, Shuzi; Li, Ping; Lin, Ping (Frontiers in Neuroscience, 2021)
Purpose of the Review Nowadays, the incidence of schizophrenia is noticeably increased. If left undiagnosed and untreated, it will lead to impaired social functions, repeated hospital admissions, decline in quality of life and life expectancy. However, the diagnosis of schizophrenia is complicated and challenging. Both genetic and environmental factors are considered as important contributors to the development and progression of this disorder. The environmental factors have been linked to changes in gene expression through epigenetic modulations, which have raised more and more research interests in recent years. This review article is to summarize the current findings and understanding of epigenetic modulation associated with pathogenesis of schizophrenia, aiming to provide useful information for futher research in developing biomarkers for schizophrenia. Recent Findings Three major types of epigenetic modulations have been described in this paper. Firstly, both DNA hypermethylation and hypomethylated have been associated with schizophrenia via analyzing post-mortem brain tissues and peripheral blood of patients. Specific changes of non-coding RNAs, particularly microRNAs and long-chain non-coding RNAs, have been observed in central and peripheral samples of schizophrenia patients, indicating their significant diagnostic value for the disease, and may also potentially predict treatment response. The correlation between histone modification and schizophrenia, however, is largely unclear. Summary Epigenetic modulations, including DNA methylation, ncRNA transcriptional regulation and histone modification, play an important role in the pathogenesis of schizophrenia. Therefore, tests of these epigenetic alterations may be utilized to assist in the diagnosis and determination of strategies of individualized treatment in clinical practice.